EFFECTIVENESS OF LAPAROSCOPY SURGERY TECHNIQUE COMPARED TO OPEN SURGERY PROCEDURE IN CHOLECYSTOLITHASIS THERAPY - Adhiyaksa, Eska; Mohamad Arifin (Fakultas Kedokteran Universitas Sriwijaya, 2025)
Laparoscopic cholecystectomy is a minimally invasive surgical technique to reduce post-operative pain and speed the recovery process. This was further demonstrated using the case of a 45-year-old man with right upper abdominal pain due to a 1.5 cm gallstone after being diagnosed via ultrasonography. The results showed that the gallstones were successfully removed via laparoscopic surgery without significant complications. Laparoscopic cholecystectomy has advantages over open surgery, because the patient's postoperative pain is lighter, recovery occurs more quickly, and the hospital stay is shorter. This technique has been proven to be effective and safer for patients without significant complications.